2000
DOI: 10.1207/s15374424jccp2901_9
|View full text |Cite
|
Sign up to set email alerts
|

Proactive and Reactive Aggression in Delinquent Adolescents: Relations to Aggression Outcome Expectancies

Abstract: Investigated whether the relation between aggression and the tendency to expect positive outcomes for aggressive behavior is specific to the proactive subtype of aggression (as opposed to the reactive subtype). In a sample of 86 incarcerated adolescent boys ages 13 to 18, we measured outcome expectancies for aggression using audiotaped hypothetical vignettes. For each participant, staff members completed proactive and reactive aggression rating scales. Regression analyses revealed that the relation between agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
98
1
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 11 publications
15
98
1
8
Order By: Relevance
“…In line with previous research (Toblin, Schwartz, Gorman, & Abou-ezzeddine, 2005), we found that t-bullying also related to children's expectations that they would gain positive results from behaving aggressively, which is associated with proactive aggression in youngsters (Smithmyer, et al, 2000) and reflects a deficit in the latter stages of the social information processing (Crick & Dodge, 1994). Our results support the suggestion of Sutton, Smith, & Swettenham (1999), that bullies do not have deficits in interpreting social cues, but in the latter stages of social information processing, during goal and response selection, where the expectancy of positive outcomes from a harmful act increases the likelihood of an aggressive response.…”
Section: Bullying and Cyberbullying 23 23supporting
confidence: 91%
“…In line with previous research (Toblin, Schwartz, Gorman, & Abou-ezzeddine, 2005), we found that t-bullying also related to children's expectations that they would gain positive results from behaving aggressively, which is associated with proactive aggression in youngsters (Smithmyer, et al, 2000) and reflects a deficit in the latter stages of the social information processing (Crick & Dodge, 1994). Our results support the suggestion of Sutton, Smith, & Swettenham (1999), that bullies do not have deficits in interpreting social cues, but in the latter stages of social information processing, during goal and response selection, where the expectancy of positive outcomes from a harmful act increases the likelihood of an aggressive response.…”
Section: Bullying and Cyberbullying 23 23supporting
confidence: 91%
“…Premeditated aggressive adults score high on measures of anger and hostility questionnaires (Stanford et al, 2003a), although children with premeditated forms of aggression do not have elevated hostility/frustration ratings (Little et al, 2003). Children with premeditated aggression tend to expect positive outcomes from aggressive actions and lack remorse or empathy regarding the use of force (Smithmyer et al, 2000), which may lead to the tendency to use aggression as a tool to achieve a desired outcome. Additionally, children who are rated as more premeditated in their use of aggression have relatively normal parent interactions, peer relations, and ratings of self-worth (Dodge et al, 1997) and are less impaired overall in comparison to their impulsive aggressive counterparts (Waschbusch et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, SIP problems in early steps (e.g., making inappropriate hostile attributions in the face of ambiguous or benign social stimuli) have been associated with reactive aggression (which has been characterized as an angry retaliatory response to perceived provocation; Dodge & Coie, 1987). In contrast, SIP problems in later steps such as evaluating aggression positively (Smithmyer, Hubbard, & Simons, 2000) and holding instrumental (e.g., obtaining a toy) rather than relational (e.g., becoming friends) goals in social interactions have been associated with proactive aggression (which is unprovoked and goal-directed; Crick & Dodge, 1996). At a broader conceptual level, the early SIP steps involve cognitions about input (i.e., taking in relevant cues from social stimuli and making attributions about others' intentions in those situations), whereas the later SIP steps involve cognitions about output (i.e., desired outcomes, possible responses, and interpretations of behavioral responses in social situations).…”
mentioning
confidence: 99%